2020
DOI: 10.1101/2020.09.15.299115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase Separation Can Increase Enzyme Activity by Concentration and Molecular Organization

Abstract: Biomolecular condensates concentrate macromolecules into discrete cellular foci without an encapsulating membrane. Condensates are often presumed to increase enzymatic reaction rates through increased concentrations of enzymes and substrates (mass action), although this idea has not been widely tested and other mechanisms of modulation are possible. Here we describe a synthetic system where the SUMOylation enzyme cascade is recruited into engineered condensates generated by liquid-liquid phase separation of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…2a). It has recently been reported that in a biochemical reconstitution of the SUMOylation cascade in engineered condensates, when two substrates were present, only the one recruited into the condensates was SUMOylated efficiently 50 . However, in this system, rate enhancement and specificity were constrained by the properties of enzymes and substrates, in manners that should be general.…”
Section: Molecular-scale Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a). It has recently been reported that in a biochemical reconstitution of the SUMOylation cascade in engineered condensates, when two substrates were present, only the one recruited into the condensates was SUMOylated efficiently 50 . However, in this system, rate enhancement and specificity were constrained by the properties of enzymes and substrates, in manners that should be general.…”
Section: Molecular-scale Functionsmentioning
confidence: 99%
“…For example, the rel ative change in reaction rate due to association with a condensate depended on the K M value for each individual substrate: substrates present at concentrations well above their K M value exhibited little change in the reaction rate upon condensate formation because the enzyme was already saturated even in the initial homogeneous solution; by contrast, when substrates were present at concentrations well below their K M value, formation of condensates produced strong reaction rate enhance ment. Thus, reaction rates for specific substrates can be enhanced upon condensate formation, whereas for others these rates will change only marginally, dictated by the substrate concentrations, K M values and degree of enrichment in the dense phase 50 . These considera tions may be important in understanding specificity of pathways such as RNAi, where thousands of different substrates can compete for the same enzyme.…”
Section: Molecular-scale Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizing cellular processes into biomolecular condensates is a mechanism to regulate biochemistry in distinct ways: altering molecular conformation and organization to promote specificity, increasing local concentration to accelerate enzymatic activity, and coupling interactions to enforce reaction directionality 1 10 . The emergent properties afforded by formation of extensive interaction networks in condensates can also enhance enzymatic activity beyond local concentration effects 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecular condensates are small droplets that structure the cell interior of eukaryotes [1,2] and prokaryotes [3][4][5]. They form by phase separation and participate in a wide range of cellular functions [6]: since they are chemically distinct from their surroundings, they can act as reaction centres [7,8], like the nucleolus inside the nucleus [9]. In particular, locally elevated concentrations can induce polymerization, as in microtubule branching [10] or in centrosomes [11,12], which additionally control the subcellular organization.…”
Section: Introductionmentioning
confidence: 99%